Japanese Foreign Direct Investment and Regional Trade - Lipworth, Gabrielle (IMF Working Papers; Working Paper, 1997)
We examine the relationship between Japanese FDI outflows, domestic and foreign fixed investment, and the exchange rate. The results indicate that aggregate FDI outflows have been driven by investment in Japan and the exchange rate, while the geographic distribution of such investment has been influenced by foreign economic conditions. We also find that FDI outflows have a temporary impact on exports but a permanent effect on imports. We find no evidence that behavior with respect to East Asia differs from that with respect to North America or Europe.